Analisis Faktor-Faktor yang Mempengaruhi Pengangguran Terdidik Lulusan Universitas di Indonesia Tahun 2005-2021 - Farid Wahyu Pratama; Eni Setyowati (Universitas Batanghari Jambi, 2022)
Educated unemployment is someone who has completed his education but has not found a job. The number of educated unemployed in Indonesia fluctuates from year to year, many factors influence it. This study aims to determine the effect of each independent variable, namely economic growth, inflation, investment and population growth rate on the dependent variable, namely educated unemployed university graduates in Indonesia. The data used in this study is quantitative secondary data with a time series in 2005-2021 obtained from the (BPS), NSWI and Bank Indonesia. The analytical tool used is OLS (Ordinary Least Square) analysis. The results of the effect validity test (t test) show that the independent variables that have an influence on the open unemployment rate for university graduates in Indonesia in 2005-2021 are Inflation and Population Growth. Meanwhile, the variables of economic growth and investment have no effect on the open unemployment rate for university graduates in Indonesia in 2005-2021.